Influence of Personal, Academic, Social, and Level of Physical Activity Variables on Emotional Intelligence - Iago Portela-Pino; José Domínguez-Alonso; Myriam Alvariñas-Villaverde; Juan José Chinchilla-Mira (MDPI AG, 2022)
In the diverse and complex society in which we live, the support that an appropriate emotional intelligence can provide to adolescents to achieve a satisfactory, balanced, and peaceful coexistence is increasing. The aim of this research was to determine whether personal, academic, and social variables influenced emotional intelligence in adolescent populations. A descriptive-inferential study was carried out with 964 students of compulsory secondary education (M = 14.18; SD = 1.28), applying the emotional intelligence scale Trait Meta-Mood Scale (TMMS-24). The results show better emotional attention in boys who practice physical exercise and have good social skills; better emotional clarity in girls who practice physical exercise and have good social skills; and better emotional repair in girls under 13 years of age, who practice physical exercise, have a good academic record and good social skills. In conclusion, a solid and specific knowledge of the personal, academic, and social variables that may influence the development of emotional intelligence in the adolescent period allows helping students in the prevention or modification of undesirable aspects they may have in their relationships with society.